Pengaruh Motivasi Kerja, Kompensasi, Lingkungan Kerja, dan Budaya Organisasi Terhadap Loyalitas Karyawan Swalayan Sangat Manis Kuala Dua - Hermawan, Andi; Firayanti, Yuni; Marhamah, Marhamah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to determine the effect of work motivation, funding, work environment, and organizational culture on employee loyalty at the Sangat Manis Kuala Dua Supermarket. This study uses a quantitative approach with a survey method, and the analysis technique used is multiple linear regression. The sample in this study amounted to 92 permanent employees. Data collection was carried out through distributing questionnaires that had been tested for validity and reliability. The results of the analysis showed an R Square value of 0.705, which means that 70.5% of the variation in employee loyalty can be explained by the four independent variables studied, namely work motivation, compensation, work environment, and organizational culture. The regression equation obtained is Y = 2.446 + 0.112 + 0.129 + 0.860 + 0.850. Partially, work motivation (t-test = 5.368), change (t-test = 6.171), work environment (t-test = 4.185), and organizational culture (t-test = 3.992) were proven to have a positive and significant influence on employee loyalty, with a significance value of 0.000 (<0.05). The results of this study emphasize the importance of maintaining these four factors continuously so that companies can maintain the loyalty and long-term commitment of their employees.